(untitled) (Global Journal of Management and Business Research, 2023)
Supply Chain Management field presents its management, consultants, and professionals with a set of various decisions to be made at the strategic, tactical and operational phases. One critical component of these decisions is the supply chain network design. Each firm, during the establishment phase, is required to properly design its network by strategically positioning its distribution facilities to optimize the overall cost of its supply chain. This paper illustrates the importance of such decision; specifically, in relation to the storage of hazardous commodity while covering strengths, weaknesses, opportunities, and threats associated with this decision. Furthermore, the paper presents a potential model for managing hazardous materials that can lead to a significant reduction in the warehousing cost; if executed properly.